Heat transfer analaysis on crude oil and petroleum products using the heat exchangers used in petroleum industries - Kanaan, Mahmood Bander (My University, 2017)
Shell-and-tube heat exchangers are utilized for the most part in the mechanical and chemical processes, petroleum industries and power plants, particularly in refineries, since various advantages they offer over different models of heat exchangers. Numerous data are available about their development and plan. The present notes are proposed only to assist as a brief introduction. It is necessary to operate heat exchangers at optimum condition which serves high thermal efficiency in acceptable conditions and low running costs. This research is planned to help anybody with general technical experience, but maybe constrained to the learning of heat transfer equipment. In this study temperatures of tube and shell side are taken as input parameters with a concurred bundle arrangement of square pitch. The thermal analysis has been done taking crude oil inside the tube and oil products on shell side. The design of shell and tube exchanger applying Kern method for combination has been proved by well-known Dittus-Boelter formula of turbulent flow inside tube. The analysis is extended by applying the Kern method above in heat exchangers with different fluid combinations and proof parameters such as heat transfer coefficient, friction coefficient, area, length and pressure drop are determined. In this study, the calculated numerical heat output from four heat exchangers was compared to those which were determined experimentally by its producer. This study focuses on finding a proof of numerical model with the real data sheet from the refinery. “MATLAB” Program has been written to evaluate the parameters above. The tables have been written to describe the behavior of different fluid combinations in different heat exchangers. The aim of this study is to prove a numerical model for the tested heat exchangers by the refinery at real experimental operating conditions in the company. The results we got are tabulated.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Heat exchangers (shell and tube); Crude oil; Kern method; Heat transfer